FLICKERING CONCEPTS OF COGNITIVE-IDEOLOGICAL MATRICES: Based on a series of sociological studies during 2015–2020 - P. Potseluev, Sergey; S. Konstantinov, Mikhail; A. Podshibyakina, Tat’yana (Gênero & Direito, 2020)
The study specifies the concept of political ideology in terms of its matrix structure, in particular the “flickering concepts” of ideological attitudes, which are hard to identify by means of traditional sociological surveys. Considering the morphological approach to the analysis of ideological consciousness (suggested by Michael Freeden), the authors introduce the concept of cognitive ideological matrices, which allows us to describe the process of transition from proto-ideological to ideological concepts, especially at the level of individual consciousness. The authors studied the above-mentioned concepts of flickering ideological consciousness in the framework of scientific projects implemented by them during 2015–2019. The studies aimed to reveal the ideological attitudes of students of Rostov-on-Don. The methodology of these projects included quantitative and qualitative analysis: in the course of group interviews, based on the material of the discourse declared by the respondents, relevant “flickering” concepts of ideological attitudes were revealed and then operationalized in the questionnaire, and the results of the survey were later falsified in focus groups. Because of the study, it was possible to first identify the “zero level” of ideology, at which the minds of young respondents are potentially open to the influence of diverse and often mutually exclusive ideological orientations, and second, to pinpoint the changes that have occurred in the cognitive ideological matrices of Rostov-on-Don students over the past five years. These changes mean that the basic concepts of left-liberal ideology are strengthening, and the right-wing “flickering concepts” are shifting to the center-left concepts of social justice, equality, etc. In general, it is common for the interviewed students to display situational ideological attitudes and indifference toward larger ideological narratives. The results of the study can be used for comparative analysis and to forecast of the ideological attitudes of Russian students.